Promising areas for improving fiscal control procedures in Ukraine - Tatarova, Tetiana; Shchupakivskyi, Roman; Shkliarenko, Andrii; Zhuravel, Oleg; Kashperska, Tamara (Amazonia Investiga, 2022)
The aim of the article is to identify promising areas for improving the procedures for fiscal control in Ukraine. The subject of the study is fiscal control of the State. The methodological basis is a number of modern methods of scientific knowledge, in particular: the method of documentary analysis, method of interpretation, monographic method, system and structural method, modeling and predicting method, etc. The results of the research can be used in both theoretical and practical areas in the framework of improving the practical activities of the actors of implementation of fiscal control procedures in Ukraine. Practical meaning. Based on the analysis of scientific views of domestic and foreign scientists and the rules of current legislation, the ways to improve the procedures for fiscal control in Ukraine are identified. Value/originality. The scientific novelty of the article is that it solves the problem of implementing procedures for fiscal control in Ukraine.